Diagnosis and treatment of emphysematous pyelonephritis in diabetic patients. - Qosimova Zuxra Madaminjanovna (Genius Journals, 2023)
One of the most severe diseases of the genitourinary system is emphysematous pyelonephritis, which is rarely observed but carries serious consequences. This article discusses cases of emphysematous pyelonephritis in combination with diabetes mellitus.
Keywords: Pyelonephritis; diabetes mellitus; emphysematous pyelonephritis; comprehensive examination